Adsorption of ?-Picoline and ?-Picoline on the Adsorbent Produced from Spent Bleaching Earth - Mahramanlioglu, Mehmet; Ozgen, Ozge (Asian Journal of Chemistry, 2010)
Adsorbents were produced from spent bleaching earth and the individual adsorption of α-picoline and γ-picoline by them was studied as a function of time, pH and initial concentration. The adsorption process for both solutes followed the first order Lagergren equation and the rate constants of the adsorption were calculated for each solute. Rate constants of intraparticle diffusion were also calculated for each solute. The adsorption capacities were obtained from the Langmuir isotherm. In order to understand adsorption mechanism, Giles isotherm was used and adsorption type for each solute was determined. Maximum adsorption capacity was observed between pH: 8.13 and 8.77.